2009
DOI: 10.1007/s12011-009-8435-5
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of the Effect of Strontium Pre-Treatment on Calcium Release From Carious and Non-Carious Teeth

Abstract: The administration of strontium salt is known to be beneficial for bones in preventing calcium loss and osteoporosis. Therefore, we decided to study if strontium treatment affects calcium release from teeth in vitro. Extracted carious as well as non-carious teeth were washed, cleaned, and dried. These were individually immersed in 25 ml of 1% lactic acid at 37 degrees C for 24 h, and the amount of calcium released was measured. The rate of calcium release from these teeth was again determined after their expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…It is quite possible that decreased strontium intake makes the teeth vulnerable to caries [9]. A possible relationship between strontium and caries is supported by (1) epidemiological studies that the lowest incidence of caries occurred in areas with strontium levels of 5.4 to 8.3 mg/L in drinking water, with increased incidence at higher and lower levels [10], (2) animal studies by Rygh [11] showing that strontium stimulates calcium deposition in bones and teeth of rats and guinea pigs, (3) experimental studies that giving strontium to rats in their diet increases the buildup of dentin in their teeth [12], (4) analytical studies reporting lower strontium level in the enamel of carious teeth compared to sound teeth [13], and (5) our own in vitro studies, simulating conditions of dental caries, showed significant decrease in calcium release from both carious as well as non-carious teeth after pretreatment with strontium salt [14]. Further, strontium is in the same group of periodic table as calcium, so has similar properties to it, but is more reactive [15].…”
Section: Resultsmentioning
confidence: 99%
“…It is quite possible that decreased strontium intake makes the teeth vulnerable to caries [9]. A possible relationship between strontium and caries is supported by (1) epidemiological studies that the lowest incidence of caries occurred in areas with strontium levels of 5.4 to 8.3 mg/L in drinking water, with increased incidence at higher and lower levels [10], (2) animal studies by Rygh [11] showing that strontium stimulates calcium deposition in bones and teeth of rats and guinea pigs, (3) experimental studies that giving strontium to rats in their diet increases the buildup of dentin in their teeth [12], (4) analytical studies reporting lower strontium level in the enamel of carious teeth compared to sound teeth [13], and (5) our own in vitro studies, simulating conditions of dental caries, showed significant decrease in calcium release from both carious as well as non-carious teeth after pretreatment with strontium salt [14]. Further, strontium is in the same group of periodic table as calcium, so has similar properties to it, but is more reactive [15].…”
Section: Resultsmentioning
confidence: 99%
“…Addition of strontium to fluoride in vitro resulted in an increased protection of enamel against fermentation attack by Streptococcus sobrinus [22] and in a significant enhancement of enamel remineralization in vitro, suggesting an interaction between fluoride and strontium when used in conjunction [23]. Exposure of enamel to strontium chloride solution in vitro reduced the loss of calcium from intact teeth or carious teeth by half when exposed to lactic acid, with no effect on enamel hardness [24]. In this study the concentration of strontium reached a peak of 5.2-5.4% in enamel and dentin.…”
Section: Discussionmentioning
confidence: 97%
“…This property of apatite explains the effect of many ions on tooth decay, viz., a wellknown effect of fluoride in the prevention of dental caries and our experimental observation of decreased calcium release in 1% lactic acid after pre-treatment of teeth with strontium chloride [15] as strontium salts are less soluble than calcium salts [14]. As can be seen from Table 1, the fluoride as well as the strontium level of blood of persons with caries was significantly lower than those having sound teeth.…”
Section: Resultsmentioning
confidence: 74%
“…The mean strontium content of carious teeth was 238 ppm as opposed to 389 ppm in non-carious sound teeth [4]. The experimental proof of beneficial effect of strontium in preventing calcium loss from teeth is provided by our recent study in which we had found that strontium pre-treatment of both carious as well as sound teeth resulted in a significant decrease in calcium released from them when immersed in 1% lactic acid [15]. A causal relationship between strontium deficiency and caries is supported by higher incidence of caries in areas with lower strontium in drinking water and vice versa [16], lower strontium in carious enamel than that of sound teeth [17] and that strontium supplementation of animals increased the buildup of bony dentin tissue in their teeth and reduced the incidence of caries [18], and our current study demonstrating strontium deficiency in the blood of persons having caries.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation